Asthma and hypertension: the role of airway inflammation - Visca, Dina; Ardesi, Francesco; Zappa, Martina; Pignatti, Patrizia; Grossi, Sarah; Vanetti, Marco; Migliori, Giovanni Battista; Centis, Rosella; Angeli, Fabio; Spanevello, Antonio (Frontiers in Medicine, 2024)
Introduction: Asthma is a chronic inflammatory respiratory disease often associated with comorbidities. Among cardiovascular comorbidities, arterial hypertension seems to create an additional health burden in asthmatics. However, evidence on this relationship is lacking Objective: Our study aims to evaluate the characteristics of hypertensive asthmatics, focusing on the role of inflammation as a possible link between these diseases.We conducted a monocentric retrospective analysis consecutively including asthmatics who underwent induced sputum (IS) at our asthma referral center. Patients were divided in two groups according to presence or absence of history of hypertension. Clinical, functional, and inflammatory (airway and systemic) data were collected.Results: Data on two hundred and sixty asthmatic patients were analyzed. Seventy-nine (30.4%) of them had a diagnosis of hypertension requiring a specific pharmacological treatment. Asthmatics with hypertension were more frequently male (p=0.047), older (p<0.001), and with higher body max index (BMI) (p<0.001) when compared to normotensive patients. No difference concerning asthma control, severity and pharmacological treatment was observed between the two groups (all p>0.05); distribution of comorbidities and lung function impairment (forced expiratory volume in the first second (FEV1) and forced vital capacity (FVC); all p<0.05) were statistically different between groups. Mixed granulocytic airway inflammation was prevalent in the hypertensive asthmatics (p=0.014). Interestingly, a multivariable analysis revealed that age ≥ 65 years and an increased percentage of sputum neutrophils (≥61%) were independent predictors of hypertensive status (p<0.001).Our data suggest that neutrophilic airway inflammation (as evaluated by induced sputum) is strictly associated with hypertension. In clinical practice, phenotyping asthmatic patients with comorbidities like hypertension could be useful also from a therapeutic point of view. Additional studies are mandatory to further elucidate the role of neutrophilic airway inflammation in asthma with cardiovascular diseases.